Describing The Principle Of Balance In The Implementation Of The Construction Work Contract - Mohammad Ramdhan Djahuno (Estudiante Law Journal, 2019)
AbstractThis paper aims to analyze the principle of balance in the implementation of construction work contracts and to describe the factors that influence the implementation of the principle of balance in construction contracts not being implemented . Type Research used _ by researcher in compile article this is type Study normative . As for approach used _ in writing this are , among others; Approach legislation (Statue Approach ) and approach case (case approach). Analysis used _ in writing this is descriptive data analysis . Results in study this is , application principle balance in relationship _ industry service The construction contract has been clearly regulated in relation to the construction contract agreement, one of the strengthening principles in the construction contract lies in the principle of balance, which requires both parties to fulfill and carry out the agreement. Creditors have the power to demand achievements and if necessary, they can pay off achievements through the debtor's wealth. However, the debtor also bears the obligation to carry out the agreement in good faith. The factors that influence the implementation of the principle of balance in the construction contract as seen from the results of the decision (jurisprudence ) include: The lack of knowledge of the parties regarding the principle of balance or the principle of construction contracts as regulated by Article 3 of Law Number 2 of 2017 concerning construction contract services, the existence of interests, the quality of the substance of the contract made, communication of the parties, the contract administration system, and the contents of the contract which is not in accordance with the implementation.Keywords: Principle of Balance; Employment contract; Construction